Penerapan Nilai-Nilai Religiusitas dalam Pembentukan Aspek Afektif Siswa Sekolah Dasar Ad-Dzikir Desa Pragaan Laok Kecamatan Pragaan Kabupaten Sumenep Tahun 2023 - Maznah Majdiyah; Uswatun Hasanah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This research uses descriptive qualitative methods. The data sources in this research are homeroom teachers and students at Ad-Dzikir Elementary School, Pragaan Village. Data collection uses interviews, observation and documentation. The data analysis technique uses Miles and Huberman's theory which includes data reduction, data presentation, and drawing conclusions or verification. Then, check the validity of the data using source triangulation by comparing the results of interviews from several informants.The results of this research are that at Ad-Dzikir elementary school, implementing (1) the application of religiosity values ​​through the midday prayer program in congregation can build discipline and responsibility; (2) The application of religiosity values ​​through memorizing juz 'Amma and surah munjiyat can shape students' affective aspects in the realm of characteristics; (3) Applying religious values ​​through instilling good behavior can shape students' affective aspects in the realm of acceptance. Meanwhile, supporting and inhibiting factors in the application of religiosity values ​​in shaping students' affective aspects, of the supporting factors there are teacher factors and parent factors. The inhibiting factors consist of the environment, family, and factors within the child.